P041 PER3 polymorphism, sleep duration and depression symptoms in a brazilian family-based cohort, the baependi heart study. (19th November 2019) - Ruiz, Francieli S; Beijamini, Felipe; Taporoski, Tamara P; Pereira, Alexandre C; Knutson, Kristen L; Pedrazzoli, Mario; Krieger, José E; Vallada, Homero; Schantz, Malcolm von
Abstract : Introduction: Circadian rhythmicity is tightly regulated by clock genes. Polymorphic variations of the human PER3 gene have been shown to influence diurnal preference, sleep homeostasis and the development of mood disorders. However, it is unclear whether polymorphisms in this gene are associated with sleep duration and depression symptoms in real-life scenarios. We have investigated the relationship between sleep duration and mood traits among PER3 genotype groups in a Brazilian family-based cohort. Methods: Baependi is a small rural town in Brazil that provides an opportunity to study the influence of sleep circadian patterns in a highly admixed rural population. We studied 1, 100 subjects (mean age±SD 47.6±15.3, 42% male) and evaluated the effects of the coding-region variable number tandem repeat polymorphism in PER3 (rs57875989) on mood (Hospital Anxiety and Depression Scale) and self-reported sleep habits (Pittsburgh Sleep Quality Index), controlling for age and sex, using a general linear model. Results: Our genotyping data showed that 33.5% of the subjects were homozygous for the shorter PER3 allele (4/4), 55.3% of participants were heterozygous (4/5) and 11.2% of subjects were homozygous for the longer allele (5/5). A main effect of PER3 genotype, sex and age was observed (p≤0.01) on depression symptoms, as well as a significant interaction between sex and sleep duration ≤7 or >7 hours. The results revealed an increase in depression symptoms in the PER3(4/4) genotype compared to PER3(4/5). It was observed also an increase in depression symptoms according to the increase of age. The depression traits were also increased in women that have reported reduced sleep duration, despite controlling for age. Discussion: We observed associations between PER3 genotype, sleep duration and depression symptoms, suggesting that PER3 gene may be behaviourally relevant for mental health, especially for women under chronic sleep loss conditions. CNPq – PVE; Academy of Medical Sciences/Newton International Fellowship